Stress Level In Ensuring Health Measures Compliance in Local Religious Ceremonies During COVID-19 Pandemic Among Pecalang in Bali - I Gede Yudiana Putra; Anak Agung Restu Anggara; Yupin Aungsuroch; I Kadek Artawan; Ni Wayan Arie Setyarini (Babali Publisher, 2023)
Background: The global covid-19 pandemic attack, especially on Bali Island, is not only causing significant loss of life but also has profoundly transformed the way of living. This situation eventually restricted the participation of Hindhus in religious ceremony activities in Bali due to strict mass gatherings measures. This study aimed to examine the stress level among pecalang (local security officers in a native administrative area in Bali) in ensuring health measures compliance in faith-based ceremonies during the Covid-19 pandemic. Method: This was a quantitative-descriptive study involving 292 pecalang in Susut District, Bangli. A purposive sampling technique was employed to select eligible participants. Fourteen stress-scale statement items in Depression Anxiety Stress Scales (DASS 42) Questionnaire used to collect primary data from the participants. Data were then analyzed using a univariate analysis in SPSS version 25. Result: The majority of participants, 184 subjects (63%), were aged between 25 to 39 years (early adulthood stage). Sixty-two percent of the participants (181) graduated from senior high school. The majority of them were also working in private companies (141: 48.3%). Findings revealed that the majority of participants were experiencing a normal level of stress (180; 61.6%). Conclusion: The majority of participants perceived normal level of stress in ensuring health measures compliance in local spiritual ceremonies during the Covid-19 pandemic.